Interstitial lung disease: a review of classification, etiology, epidemiology, clinical diagnosis, pharmacological and non-pharmacological treatment - Althobiani, Malik A.; Russell, Anne-Marie; Jacob, Joseph; Ranjan, Yatharth; Folarin, Amos A.; Hurst, John R.; Porter, Joanna C. (Frontiers in Medicine, 2024)
Interstitial lung disease (ILD) is an umbrella term for approximately 200 different diseases that may result in inflammation and scarring of the lung tissue (Figure 1) [1]. ILD is characterised by progressive dyspnoea, cough, hypoxia, impaired lung function, diffuse bilateral infiltrates on imaging, inflammation, fibrosis, limited patient mobility and reduced quality-of-life (QOL)[2]. Most ILD cases result from an aetiological factor, such as exposure to allergens, hazardous material, asbestos, drugs or an underlying autoimmune disease [1-4]. The development of these cases is a complex process that is influenced by a variety of factors, including the individual's genetic traits, and exposure to environmental pollutants [5]. Idiopathic Pulmonary Fibrosis is the most aggressive form of ILD, causing progressive and permanent lung scarring. It causes a chronic and irreversible lung disease with a poor prognostic outcome with a median survival rate of 3-5 years post-diagnosis [4, 6, 7]. Although two antifibrotic medications demonstrated a significant reduction in the rate of disease progression, it remains difficult to predict disease behaviour for individual patients [4, 6, 7]. The purpose of this review is to provide up-to-date information on interstitial lung disease (ILD), with a particular emphasis on definition, classifications, aetiology, epidemiology, diagnosis, pharmacological and non-pharmacological management.